IMPLEMENTASI KURIKULUM BAHASA INDONESIA ANTARA HARAPAN DAN KENYATAAN - Nursalim Nursalim (Sosial Budaya, 2011)
Abstraction: This Study copes to open Big Outline implementations of Program Instruction (GBPP) Indonesian Subject at Set Mount Curriculum Of Education (KTSP), Elementary School (SDN) in school activity (KBM) in the class. The purpose of this Study is to: (1) knowing whether teacher fulfill instruction procedure " fairly", (2) compiling planning and execute instruction in class as according to time which is allocated, and also ( 3) using method correctly. The result of class observation and interview to teachers of 9 classes of V SD in various Town in Pekanbaru Riau region indicate that time allocation provided in GBPP Indonesian assessed by having adequate but, some teacher is not exploited yet the time efficiently and effectively. The teacher generally is not owned yet a good ability in the plan and KBM execution. Packet Book is pledged as reference of teaching than the planning reference which they should compile. The purpose of Ianguage Instruction is in order that the student is able to read, correct in reading, writing, and listening, has not obtained yet the proporsional attention.